Analysis of Circular Waste Using a Causal Loop Diagram (CLD): A Case Study of Sukabumi City: Studi Kasus Kota Sukabumi - Eneng Rahmi; Lioba Evita Anikusuma (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the transition from linear to circular municipal solid waste management in Sukabumi City using a system dynamics approach. Utilizing a qualitative descriptive design, data were gathered through surveys of 400 residents across 33 villages, field observations of waste facilities, and stakeholder interviews. Results reveal significant "lost circularity" driven by low source separation, negative public perceptions, and the underutilization of community-based 3R facilities (TPS3R) and waste banks. The developed Causal Loop Diagram (CLD) identifies five reinforcing loops which are centred on 3R participation, institutional collaboration, and material value—and four balancing loops related to infrastructure limits, behavioural resistance, and funding constraints. The dominance of these balancing loops explains the stagnation of the circular transition. Findings suggest that the system remains trapped in a "take–make–dispose" model due to operational bottlenecks. The study concludes that the primary leverage points for accelerating circularity include intensive 3R education, the reactivation of upstream infrastructure, and enhanced multi-actor collaboration. These interventions are essential to shift the system dynamics toward sustainable resource recovery and reduced landfill dependency.